Pembiasaan Menjaga Kebersihan pada Santri di TPQ Al-Iman Desa Bulak Kendal Ngawi - Nurul Anisa Fitri; Dwi Lestari; Yusron Luthfil Khuluq; Hafaruli; Alsa Permata Yuniarti (Jurnal Abdikarya Pembangunan, 2023)
Abstract: Lack of awareness of TPQ Al Iman Bulak students requires intervention in the form of habituation activities that make students able to implement and maintain environmental cleanliness, especially. This intervention is important because there are still many students at TPA Al-Iman who are at the stage of child development which plays a role as laying the foundation for the character of the students to be able to respect their environment. This service uses an action research approach in which the process is carried out by involving students, teachers and the surrounding community.The habit of clean living is the formation of behavior that is relatively permanent in students which is carried out repeatedly with a series of activities. Providing hadith material for cleanliness through rote memorization with the meaning of making students understand the value of cleanliness taught in Islam. Tadabur alam makes students learn that all creatures in nature have their respective functions and require real action to preserve them. While the practice of cleaning mosques and prayer rooms provides direct experience in managing space and maintaining cleanliness when worshiping. The visible impact of the change is that the environment is getting cleaner because there is fulfillment of hygiene facilities. Increased convenience and order. While for the students themselves the knowledge and values of cleanliness are increased in the hadith of the Prophet. Habituation must be strengthened by sustainable activities such as making pickets for cleaning students, making regulations and synergizing with the community in the surrounding environment. Keywords: Habituation, Maintain Cleanliness, Santri, TPQ Abstract: Kurangnya kesadaran santri TPQ Al Iman Bulak membutuhkan intervensi berupa kegiatan pembiasaan yang membuat santri mampu menerapkan dan menjaga kebersihan lingkungan terutama. Intervensi ini menjadi penting karena santri di TPA Al-Iman masih banyak yang berada pada tahap perkembangan anak yang berperan sebagai peletakan pondasi karakter santri untuk bisa menghargai lingkungannya. Pengabdian ini menggunakan pendekatan action research yang prosesnya dilakukan dengan melibatkan santri, pengajar dan masyarakat sekitar. Pembiasaan menjaga kebersihan merupakan pembentukan perilaku yang relatif menetap pada diri santri yang dilakukan secara berulang dengan serangkaian kegiatan. Pemberian materi hadist kebersihan melalui hafalan dengan arti membuat santri mengerti nilai kebersihan yang diajarkan dalam Islam. Tadabur alam membuat santri belajar bahwa semua mahluk dialam memiliki fungsinya masing- masing dan memerlukan tindakan nyata untuk melestarikannya. Sedangkan praktik membersihkan masjid dan mushola memberikan pegalaman langsung dalam menata ruang dan menjaga kebersihan ketika beribadah. Dampak perubahan yang terlihat adalah semakin bersihnya lingkungan karena ada pemenuhan sarana kebersihan. Peningkatan kenyamanan dan ketertiban. Sedangkan pada diri santri bertambahnya pengetahuan dan nlai kebersihan yang ada dalam hadits nabi.pembiasaan harus dikuatkan dengan kegiatan yang berkelanjutan seperti pembuatan piket kebersihan santri, pembuatan peraturan dan sinergi dengan masyarakat di lingkungan sekitar. Keywords: Menjaga Kebersihan, Pembiasaan, Santri, TPQ